“Você seria tão bonita, se fosse magra”: Os múltiplos sentidos no discurso da superação da obesidade - Picagevicz, Ana Paula (2018)
This study aims to analyze, from the theoretical-methodological assumptions of the Discourse Analysis of French orientation, the processes of production of meaning in the transmission of news, in the electronic newspaper G1, referring to the overcoming of obesity. For the construction of the corpus of this work, we sought to cut discursive sequences from the news produced and conveyed by the G1 portal "O Portal de Notícias da Globo" between 2012 and 2016, in order to understand the "need" to overcome the obstacle that is the fat body, put as the greatest villain to achieve the goal of "success" portrayed in the lean body and so learn the sense effects of this fat body and lean body nowadays. The fact is, fatness and thinness have always existed. However, the fat body that in many societies was welcomed and seen with "good eyes" while thinness was synonymous with disease, today "needs" to make an effort to lose weight and prevent the body from being an obstacle to enter into everywhere and be accepted in society. In this scenario, the media collaborates as a diffuser of this "need", because it is impregnated with cultural references, aided by the market, generates consumption and builds ideals of beauty and body patterns. It gains its space in society for being an omnipresent text to interpellate the subjects with sayings about qualities alienated the modern social life, dictating to the subjects, that they need to fill their life through something that is outside of them. This dominant statement that is given by the media crossed by the market is what regulates and establishes conduct, customs and social tastes. In this way, the construction of meanings around the fat body is always negatively adjectivized, as a body that violates the laws in force. It is therefore a transgressor, while the lean body is positived and exalted, a fact that emerges from the mediatic perspective and is guided by the culture of consumption, shows a place of construction of this subject that is seduced by the "impositions" of success, translating an "illusion of completeness, "conveyed as the" formula of full happiness "and illustrated in the form of gains, self-esteem, beauty, professional, personal and loving ascension. In the workings of journalistic discourse, the search for the meaning of the news is built on the idea that language and history are transparent. These questions allow us to understand the ideological functioning of these senses about body and beauty, about health, about success intervening in the life of the subject, who builds his body in consumption and, therefore, a capital body, a currency of exchange, which in effect, in the name of the results the ends erase the means, for what matters and being thin.